2004
DOI: 10.1152/ajpheart.01120.2003
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold topography alters intracellular calcium dynamics in cultured cardiomyocyte networks

Abstract: Structural and functional changes ensue in cardiac cell networks when cells are guided by three-dimensional scaffold topography. We report enhanced synchronous pacemaking activity in association with slow diastolic rise in intracellular Ca2+ concentration ([Ca2+]i) in cell networks grown on microgrooved scaffolds. Topography-driven changes in cardiac electromechanics were characterized by the frequency dependence of [Ca2+]i in syncytial structures formed of ventricular myocytes cultured on microgrooved elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 33 publications
2
58
0
Order By: Relevance
“…The expression of the calcium channel α1C subunit and peak values for I to , I Na , and I Ca are all increased for aligned neonatal rat ventricular myocytes compared to pleomorphic cultures [181]. Furthermore, tissues aligned with microgrooved substrates show increased systolic intracellular Ca 2+ and decreased diastolic rise time [187]. These studies suggest that cytoskeletal architecture can regulate electrophysiology and furthermore indicate that an aligned phenotype similar to that observed in vivo is optimal for ion channel expression and function.…”
Section: Excitabilitymentioning
confidence: 74%
“…The expression of the calcium channel α1C subunit and peak values for I to , I Na , and I Ca are all increased for aligned neonatal rat ventricular myocytes compared to pleomorphic cultures [181]. Furthermore, tissues aligned with microgrooved substrates show increased systolic intracellular Ca 2+ and decreased diastolic rise time [187]. These studies suggest that cytoskeletal architecture can regulate electrophysiology and furthermore indicate that an aligned phenotype similar to that observed in vivo is optimal for ion channel expression and function.…”
Section: Excitabilitymentioning
confidence: 74%
“…Many studies have previously associated cellular alignment and sarcomeric organization with improved Ca 2+ physiology of NRVM on structured tissue substrates. 11,[25][26][27] These observations have been primarily attributed to changes in the sarcoplasmic reticulum organization 28 and voltage-gated Ca 2+ currents. 3 Therefore, it is not surprising that Ca 2+ handling parameters of NRVM were similar for cells cultured on both film thickness groups.…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) cell cultures have a wide variety of applications in basic cell and tissue studies (Yin et al, 2004;Entcheva and Bien, 2003;Motlagh et al, 2003), in vivo tissue repair and clinical practice (Curtis et al, 2005;Stoklosowa, 2001). Previous studies have attempted to provide grooved surfaces for cardiomyocytes to mimic their in vivo 3D circumstances, and have shown that the alignment, orientation and shape of the cells were guided by the grooved surfaces (Yin et al, 2004;Entcheva and Bien, 2003;Motlagh et al, 2003).…”
Section: Introductionmentioning
confidence: 99%